GAMBARAN WORK LIFE BALANCE PADA MAHASISWA MAGANG MSIB BATCH 6 DI JAKARTA - Theresia Angela, De Vercelli; Andreas , Jonatan; Irene , Irene; Komang Ayu , Chandra; Zamralita , Zamralita (Fakultas Psikologi Universitas Tarumanagara, 2024)
Students have the opportunity to work in real life or internship activities to channel the theory that has been obtainedin lectures. The purpose of internship activities is to provide students with a real picture of the world of work, so thatstudents can get used to it and have a high level of work readiness after graduation. Lecture activities and workschedules result in dual roles resulting in difficulty achieving work-life balance. Work-life balance is a balance of theuse of time, energy, goal achievement, and tension in work and personal life. The purpose of this study was to see apicture of work-life balance in MSIB Batch 6 internship students in Jakarta. This study used a quantitative methodwith 107 participants. This study uses the Work/Nonwork Interference and Enhancement Scale measuring instrumentprepared by Fisher and has been adapted into Indonesian. Reliability in this study α = 0.847 Meanwhile, validitytesting shows 0.302 - 0.753 > 0.188, P = 0.00 < 0.05 and Pearson Correlation is positive, so this study is valid. Theresults of this study indicate that the normality test was carried out using the one sample Kolmogorov-Smirnov testmethod (P = 0.000 <0.05) so that the data in the study were said to be not normally distributed. This study shows thatthere is no difference in work-life balance between women and men (P = 0.174 > 0.05), there is no difference basedon the age of the participants (P = 0.335 > 0.05), there is no difference based on the semester of the internship (P =0.348 > 0.05). The results of this research show that the average work-life balance score for MSIB Batch 6 internstudents is 2,664, this score is considered low using the Likert scale calculation.